REFORMULATING THE ROLE OF EDUCATORS IN ICT ERA - Miftah, M (Indonesian Journal of Early Childhood Education Studies, 2013)
Contribution or support of information technology toward education technology is necessarily needed to reach the learners wherever they are. Besides, it also functions to serve most learners who havenât got the chances to learn, to accomplish the need of learning in order to keep abreast of the changing times, and to improve efficiencies and effectiveness of learning and academic services. This article aims at reformulating roles and functions of educators in the era of information and communication technology (ICT). This article discusses: (1) the changing of academic advising services through ICT; (2) the ICT-based academic guidelines and advising system; (3) the advantages and weaknesses of academic advising through on-line model; (4) the ICT-based academic advising roles and services; (5) the ICT-based academic advising ethic.